The paradox of water management projects in Central Asia: An institutionalist perspective - Lioudmila Chatalova; Nodir Djanibekov; Taras Gagalyuk; Vladislav Valentinov (Water, 2017)
After the disintegration of the Soviet Union, the Central Asian countries have been faced with numerous development challenges in agriculture, especially those related to water use. Well-intentioned foreign donors and development agencies have stepped in to support local farmers, research centers, and public authorities in devising innovative solutions. Yet, development aid projects have borne fruit only partially. Paradoxically, innovative and apparently useful technologies proposed by foreign donors have rarely and only partially succeeded in taking root in the local institutional contexts. To explain this paradox, this paper draws on the institutional approach which shows the possibility of technological innovations being encapsulated by dysfunctional institutions. Reviewing recent studies of water-related projects in Central Asia, the paper shows this encapsulation to be at the core of the development project failures pervasive both in the Soviet period and today. If the concept of encapsulation is valid, then the current development efforts can be made more effective by detecting and counteracting the structures of vested interest on the part of all the actors involved, such as foreign donors, public authorities, research centers and local farmers.
Keywords: 330; Central Asia; water use; development projects; innovation adoption; institutionalist dichotomy; Veblen; transition economy